Komunikasi Konflik Dalam Pengelolaan Sumberdaya Perikanan Di Kawasan Taman Nasional Karimunjawa (Kasus: Desa Karimunjawa, Kecamatan Karimunjawa) - Titania Aulia; Sarwititi Sarwoprasodjo; Arif Satria (Institut Pertanian Bogor, 2015)
Differences of perception in the fisheries resources management in the area of Karimunjawa National Park (KNP) is still perceived by all stakeholders, especially the Karimunjawa National Park Officer (KNPO) as authorities. As KNPO, attempts to communicate with the fishermen, even with using of communication media, such as notice boards, poster, leaflet, and implementation of the No Take Zone Campaign Program. Fishermen believe that the lack of information due to lack of communication, so KNPO regarded as enemies of fishermen. The purpose of this study was to analyze the perception of fishermen on aspects of fisheries resources management, resulting in conflict due to differences in perception. This study has revealed that the social characteristics (age and experience of fisheries resources management) and trust of KNPO correlated to perception of fishermen in fisheries resources management aspects. The characteristics of fishermen who have different perceptions with KNPO were fishermen who lived near KNPO office, fishermen who did not participate in the activities of KNPO, young age, and fishing experience is still lacking. Keywords: communication media, perception, conflict